Using BEA to Select Skill and/or Performance Interventions for Oral Reading Fluency - Axelrod, Michael I.; Coolong-Chaffin, Melissa (My University, 2017)
This project examined how Brief experimental analysis (BEA) procedures could be used to identify potentially effective skill and/or performance-based interventions targeting reading fluency for 10 students (grades 1-5) who demonstrated inadequate reading performance during the school year. In addition, an extended analysis was conducted to determine the effectiveness of the indicated intervention over time when used within the context of a comprehensive reading instructional package delivered during a summer reading program. Results indicated that a promising intervention was identified for each participant. In addition, the intervention led to large gains in words read correctly per minute during the reading program on intervention passages. Variable results were seen on generalization passages. These results extend the literature on BEA by demonstrating its use with interventions utilizing skill and/or performance-based interventions. The results also demonstrate how BEA-indicted interventions can be used within the context of a comprehensive instructional package for struggling readers during the summer.
Color poster with text, charts, and graphs.
Keywords: Brief experimental analysis; Oral reading fluency; Posters